2007
DOI: 10.4314/nifoj.v25i1.33669
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of the African locust bean (<i>Parkia biglobosa</i>) fruit pulp

Abstract: Nutritional and anti-nutritional composition of the African locust bean (Parkia biglobosa) fruit pulp were determined using standard methods. Results showed a moisture content of 8.41%, protein 6.56%, fat 1.80%, crude fibre 11.75%, ash. 4.18% and carbohydrate of 67.30%. Sugar content was found to be 9.00 °Brix; total caroteniods, 49,175ug/ 100g and ascorbic acid (Vitamin C) of 191.20mg/100g. Anti-nutritional factors/toxins analyzes showed a phytic acid content of 60.00mg/ l00g; crude saponins, 17.80mg/ 100g; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 5 publications
5
54
1
Order By: Relevance
“…Lipolysis and proteolysis are very important for the quality of African locust bean-based condiments fermented by Bacillus spp. [5] [7]. Proteolysis has been reported as the main metabolic activity during the fermentation of African locust bean [8] [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipolysis and proteolysis are very important for the quality of African locust bean-based condiments fermented by Bacillus spp. [5] [7]. Proteolysis has been reported as the main metabolic activity during the fermentation of African locust bean [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [1]- [4] show that locust bean is highly digestible (74% -97%) with pepsin followed by trypsin. This is coupled with its high commercial values as food and medicinal agent [5] [6]. Lipolysis and proteolysis are very important for the quality of African locust bean-based condiments fermented by Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that n-hexane is a very good solvent to be considered for the extraction of antibiotic-resistant modulating biomolecules present in the bark of P. biglobosa. Although we did not run an assay to investigate side effects of n-hexane fraction of P. biglobosa on eukaryote cells, experimental reports from researchers such as [11,[66][67][68] and the use of this plant in herbal medicament in some African countries (e.g., Mali, Cote d'Ivoire and Nigeria) prove that the fraction has negligible toxicity to eukaryotic cells. This explains the reason for the successful and wide usage of the plant in folklore medicine and suggests that formulations should be prepared for in vivo assay in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of locust bean fruit pulp flour was done using the method of Gernah et al (2007). The outer brown cover of the pods was manually stripped open and the yellow fruit pulp was separated from seeds embedded within the pulp.…”
Section: Preparation Of Locust Bean Fruit Pulp Flourmentioning
confidence: 99%
“…E-mail: umaruzakari44@yahoo.com from various cereals and legumes has been done to substitute wheat in baked products (Eneche, 1999, Nochera andCaldwell, 1992). The African locust bean (Parkia biglobosa) fruit pulp, which has been found to have good nutritional value (prot 6.56, fat 1.8, CHO 67.30, ash 4.18 and crude fibre 11.75%) and low antinutrients/toxins (phytic acid 60.00, crude saponin 17.80 and tannin 18.00 mg/100 g), has not been widely exploited as raw materials in confectionery products (Gernah et al, 2007;Akoma et al, 2002, Musa et al, 2005. The aim of this study was to produce biscuits from various blends of wheat flour and African locust bean fruit pulp flour and to evaluate the physical, chemical and sensory properties of the developed products.…”
Section: Introductionmentioning
confidence: 99%